IDENTIFIKASI PENGGUNAAN LAHAN BERDASARKAN SUMBER PRASASTI ABAD KE-11 MASEHI DI JAWA TIMUR - Siswanto Siswanto (Pubawidya: Jurnal Penelitian dan Pengembangan Arkeologi, 2018)
This article discusses the use of ancient Javanese ancient land based on the source of the 11th century AD inscription in East Java. The problem in this paper focus on what kind of land use during the ancient Javanese period based on the inscription of the 11th century AD. Inscriptions as the main data were studied using the epigraphic method. Analysis based on the source of the inscription that provides complete information about the life of ancient Javanese in relation to land use. The results of the inscription analysis indicate that there are six forms of land use that have been done, namely; settlements, rice fields, gardens, dams (and also canals), religious buildings, and forests. Forms of land use in the form of rice fields, gardens, dams and canals associated strongly with agricultural activities. Reasons related to land use indicate the dominance of strong political reasons. This is because in the 11th century AD especially during the Airlaṅga and its successors were the events of war and the enforcement of power so that many inscriptions contain political reasons. Although some inscriptions contain religious reasons but the numbers are not too many. However, it remains the political reason that dominates in the inscription description.